2022
DOI: 10.1111/ene.15492
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell repopulation dynamics and drug pharmacokinetics impact SARS‐CoV‐2 vaccine efficacy in anti‐CD20‐treated multiple sclerosis patients

Abstract: Background and purpose Recent findings document a blunted humoral response to SARS‐CoV‐2 vaccination in patients on anti‐CD20 treatment. Although most patients develop a cellular response, it is still important to identify predictors of seroconversion to optimize vaccine responses. Methods We determined antibody responses after SARS‐CoV‐2 vaccination in a real‐world cohort of multiple sclerosis patients ( n = 94) treated with anti‐CD20, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…In summary, our findings suggest that anti-CD20 dose interval extension could be considered in patients with RRMS with stable disease without incurring risk of return of inflammatory disease activity in the short to medium term, especially in case of treatment-related adverse events or when planning pregnancy. Further studies are needed to determine whether dose interval extension is also associated with a lowered risk of infection, while it has been shown that vaccination responses are improved with B-cell repopulation, 27 in turn improving benefit-risk with anti-CD20 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our findings suggest that anti-CD20 dose interval extension could be considered in patients with RRMS with stable disease without incurring risk of return of inflammatory disease activity in the short to medium term, especially in case of treatment-related adverse events or when planning pregnancy. Further studies are needed to determine whether dose interval extension is also associated with a lowered risk of infection, while it has been shown that vaccination responses are improved with B-cell repopulation, 27 in turn improving benefit-risk with anti-CD20 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rituximab concentration was also studied in relation to SARS‐CoV‐2 immunity. 15 In a cohort of patients with MS with variable intervals from the last infusion to vaccination (0.2–2.8 years) and consequently rituximab levels below the detection limit in 55% (33/60), rituximab concentrations were associated with humoral responses after vaccination. We show that also in the approved interval of 6 months, ocrelizumab drug concentration is a good predictor of the humoral response.…”
Section: Discussionmentioning
confidence: 95%
“…112 113 Extended interval dosing and redosing pending B-cell repopulation are strategies that may be beneficial for vaccine seroconversion and are reasonable to consider if patients are at low risk for an inflammatory event but high risk for severe COVID-19. 114 115…”
Section: Covid-19 Infection In Patients With Established Neuroimmunol...mentioning
confidence: 99%